Incremental Prognostic Value of the Admission Systemic Immune-Inflammation Index Beyond BISAP for Early Risk Stratification of Acute Pancreatitis in the Emergency Department - Ömer Damar; Mahmut Yaman (Journal of Clinical Medicine, 2026)
Background: Early identification of patients at risk of severe acute pancreatitis (AP) remains a clinical priority. We evaluated whether the admission Systemic Immune-Inflammation Index (SII, ×109/L) adds prognostic value to the BISAP score, alone and in combination. SII integrates neutrophil, lymphocyte, and platelet counts from the routine complete blood count. Methods: In this retrospective single-center cohort, 523 adults with AP (January 2020–December 2025) were classified by the Revised Atlanta Classification. Admission SII and BISAP were related to severe AP, intensive care unit (ICU) admission, and in-hospital mortality using logistic regression, ROC analysis with DeLong comparison, 1000-sample bootstrap validation, and decision curve analysis. Results: Severe AP occurred in 48 patients (9.2%), ICU admission in 61 (11.7%), and death in 26 (5.0%). Admission SII was markedly higher in severe than non-severe disease (4085 vs. 1499; p < 0.001). Both SII and BISAP independently predicted all three outcomes after mutual adjustment (severe AP: SII odds ratio 2.12 and BISAP odds ratio 4.92 per standard deviation). For severe AP, the combined BISAP + SII model outperformed either marker (AUC 0.954 vs. 0.911 and 0.917), as it did for mortality (0.957); for ICU admission SII was the strongest single marker (0.869) and the combined model did not significantly improve discrimination compared with SII alone (DeLong p = 0.287). Internal validation showed adequate calibration with modest optimism and suggested potential net clinical benefit across the evaluated threshold ranges, pending external validation. Conclusions: Combining the admission SII with the BISAP score provides incremental prognostic information beyond BISAP alone for the early risk stratification of severe acute pancreatitis and in-hospital mortality using data already available at presentation. External, prospective validation is warranted before routine adoption.